(untitled) (Research, Society and Development, 2022)
Fungal diseases need to be better known and studied, as they are not the first diagnostic hypotheses and are the main causes of morbidity and mortality among immunocompromised patients. Main agents involved in opportunistic mycoses: Cryptococcus spp., Candida spp., Aspergillus spp. and Pneumocystis spp., present epidemiological data of these infections are modest, due to incorrect or incomplete diagnoses. adding to this the indiscriminate use of antifungal agents contributed to a change in the epidemiological profile and selecting resistant fungal strains, increasing the mortality rate in affected patients. Thus, this study aims to review the literature on the main opportunistic fungi and address important aspects of the resistance profile of filamentous opportunistic fungi. A search was carried out in the scientific literature based on the electronic database Pubmed, MedlinePlus, Scientific Electronic Library Online (Scielo), Academic Google., using as descriptors: Filamentous Fungi, Antifungals; Aspergillus spp.; Candida albicans; Cryptococcus neoformans; Sporothrixs chenckii; resistance, resistance in opportunistic mycoses and resistance profile. Studies indicate that rapid diagnosis and the choice of the correct drug can increase the recovery rates of patients with fungal infections. The delay in diagnosis and even the use of drugs with low efficiency has aggravated and, at the same time, increased the mortality of patients infected with these mycoses. This study aims to increase the bibliographic base on opportunistic mycoses cases and their resistance to the main antifungal drugs available.